Asatidz's Efforts in Increasing Santri's Motivation to Memorize at the Bustanul 'Ulum Jayasakti Women's Tahfidzul Qur'an Islamic Boarding School in Central Lampung - Hikmah, Lailatul; Munir, Miftahul (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This study explores how ustadz and ustadzah foster students’ motivation to memorize the Qur'an at Pondok Pesantren Tahfidzul Quran Putri Bustanul Ulum. Employing a qualitative approach through observation, interviews, and participatory methods, the research applies the Miles and Huberman analysis model to examine motivational strategies used by educators. The findings reveal that individualized mentoring, empathetic communication, and consistent reinforcement significantly boost students’ memorization drive. The study’s novelty lies in its contextual focus on female Islamic boarding schools and its identification of integrative teaching strategies that link spiritual and academic development. This research offers new perspectives on motivation theory within Islamic education and presents practical implications for enhancing student engagement in faith-based learning environments.